Which variables explain decisions on IMF credit? An extreme bounds analysis - Jan-Egbert Sturm; Helge Berger; Jakob de Haan (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2004)
This paper analyses which economic and political factors affect the chance that a country receives IMF credit or signs an agreement with the Fund. We use a panel model for 128 countries over the period 1972-1998. Our results, based on Extreme Bounds Analysis, suggest that it are mostly economic variables that are robustly related to IMF lending activity, while most political variables that have been put forward in previous studies on IMF involvement are non-significant. To the extent that political factors matter, they seem more closely related to the conclusion of IMF agreements than to the disbursement of IMF credits.
Keywords: F33; 330; IMF credit; political economy